Disturbance, carbon physicochemical structure, and soil microenvironment codetermine soil organic carbon stability in oilfields - Yang, Juejie; Wang, Jian; Li, Aiyang; Li, Guanghe; Zhang, Fang (Environment international, 2020)
[Display omitted] •Oil contamination led to the increase of soil organic carbon (SOC) stability.•Changes of C physicochemical structure are consistent with overall SOC stability.•Disturbance, C physicochemical structure and soil properties codetermine stability.•A quantitative characterization of each factor to SOC stability is provided. The stability of soil organic carbon (SOC) is crucial for soil quality, fertility, and natural attenuation processes of pollutants. The physicochemical structures of SOC were believed to control its stability, yet has become controversial. Here we hypothesized that disturbance intensity and variations in the soil environment can also influence the SOC stability, and conducted a case study with oil contaminated soils to quantify the contributions to SOC stability of various factors including contamination level, carbon physicochemical structure, and soil properties. Oil contamination led to increased SOC stability, as suggested by appreciably decreased soil CO2 fluxes, the enrichment of the δ13C in the oil contaminated soils, as well as analysis of soil aggregates and humic substances. Redundancy analysis indicated that overall SOC stability were highly correlated to microaggregate (M2), HA/FA, Fe, soil porosity, EC, pH, and total petroleum hydrocarbon (TPH) in oilfields. Variance partitioning analysis showed that carbon physicochemical structure (S), soil properties (P), and oil contamination (O) could explain the variance of overall SOC stability by up to 90%, while 18% of the variation was explained by S × P and 43% by S × P × O. These results show that multiple factors of the disturbance, carbon physicochemical structure, and soil properties should be essential for future studies of SOC stability.